Whom to ask? Testing respondent effects in household surveys - Nathan Fiala; Lise Masselus (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
The common practice in household questionnaires of surveying the most knowledgeable household member can lead to inaccurate data if they have limited information. Using survey experiments in Paraguay and Uganda, we investigate whether there are discrepancies in intra-household reporting on income and consumption when multiple household members are interviewed. We use data from 4,100 households where we randomly vary whether the survey is administered to one spouse only, both spouses together or both spouses separately. We do not find meaningful systematic differences in the mean or distribution of household income and consumption and conclude that the magnitude of respondent effects for these variables is unlikely to bias most empirical analyses. However, a within-household analysis reveals large, but mostly unsystematic, reporting discrepancies. Taken together, the results indicate that respondent selection may matter for obtaining accurate information for a given household, but not for aggregate analysis of households. – – Die bei Haushaltsbefragungen übliche Praxis, das sachkundigste Haushaltsmitglied zu befragen, kann zu Messfehlern führen, wenn diese nicht über vollkommene Informationen verfügen. Anhand von experimentell variierenden Befragungen in Paraguay und Uganda untersuchen wir, ob es zu Diskrepanzen bei Haushaltsangaben zu Einkommen und Konsum kommt, wenn mehrere Haushaltsmitglieder befragt werden. Wir erheben Daten von 4,100 Haushalten, bei denen wir variieren, ob nur ein Ehegatte, beide Ehegatten zusammen oder beide Ehegatten getrennt befragt werden. Der Vergleich der Stichprobenmittelwerte und der Verteilungen des Haushaltseinkommens und -konsums zeigt, dass es keine bedeutenden systematischen Unterschiede gibt. Wir schließen hieraus, dass das Ausmaß der Befragteneffekte bei diesen Variablen nicht zu einer Verzerrung der meisten empirischen Analysen führen dürfte. Der Vergleich innerhalb des Haushaltes zeigt jedoch große, aber zumeist unsystematische Diskrepanzen bei den Angaben. Zusammengefasst deuten die Ergebnisse darauf hin, dass die Auswahl der Befragten für den Erhalt von genauen Informationen für einen bestimmten Haushalt eine Rolle spielen kann, jedoch nicht für die aggregierte Analyse von Haushalten.
Keywords: O1; C8; J16; D13; I32; 330; Survey methods; respondent effects; proxy reporting; intra-household economics